Savings and investment fiscal policies: A quantitative analysis for the Italian economy - Anna Ruocco (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1995)
This paper is mainly concerned with the real effects of different kinds of savings/investment incentives on the capital accumulation. Investment incentive programmes, at least in Italy, have been part of the Standard government budget for a long time. Therefore, especially from a policy-maker point of view, it is interesting to find out which are the quantitative impacts of these programmes. In particular the focus has been concentrated on: a) sector specific incentives to capital services; b) fiscal deductions on the income tax base and subsidies to purchasers of assets which qualify for the programme. These incentives schemes have been analysed performing numerical simulation of equal-yield tax changes within a general equilibrium growth model for Italy with overlapping generations. An intertemporal model has been used since the political discussion encompassing policy initiatives, such as the investment programmes, revolves around the steady-state effects rather than the static ones.
Keywords: 330; Investitionspolitik; Sparförderung; Wirkungsanalyse; Allgemeines Gleichgewicht; Wirtschaftswachstum; Overlapping Generations; Ökonomischer Anreiz; Simulation; Italien